Imaging of Pediatric Paranasal Sinus and Orbital Infections - Winegar, Blair A.; Udayasankar, Unni K. (Journal of Pediatric Neurology, 2017)
Upper respiratory tract infections are the most frequent outpatient disease processes treated by the pediatricians. Although upper respiratory tract infections are typically self-limited viral illnesses, a subset of children will develop acute bacterial sinusitis, which is differentiated from the former viral nasopharyngitis by prolonged illness, worsening course, or severe onset of symptoms. Although diagnostic imaging is not indicated in the differentiation of a viral upper respiratory tract infection from acute bacterial sinusitis, contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) are critical in the detection and classification of potentially serious complications of acute bacterial sinusitis resulting from intraorbital or intracranial spread of infection. Orbital infections are the most frequently associated complications of paranasal sinus inflammatory disease given the proximity of the paranasal sinuses and orbits. Imaging is essential in differentiating preseptal cellulitis from orbital cellulitis and guiding appropriate therapy. Cross-sectional imaging is also important in the characterization of noninvasive fungal sinusitis, forms of chronic sinusitis in the setting of an intact immune system, and invasive fungal sinusitis, an acute fulminant sinusitis induced by angioinvasive fungi in immunocompromised children requiring emergent surgical management.
Keywords: upper respiratory tract infections; cross-sectional imaging; contrast-enhanced CT; contrast-enhanced MRI